2021
DOI: 10.1097/pep.0000000000000818
|View full text |Cite
|
Sign up to set email alerts
|

How Did the Lockdown Imposed Due to COVID-19 Affect Patients With Cerebral Palsy?

Abstract: This study investigated the change in mobility, pain, functional status and spasticity in a pediatric rehabilitation unit after the lockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
1
16
0
3
Order By: Relevance
“…There are studies that have explored the impact of the COVID-19 pandemic on the practice of therapists, on mental health and the use of telerehabilitation strategies by therapists during the period of confinement ( Dogruoz Karatekin et al, 2021 ; Ganesan et al, 2021 ). As healthcare personnel who have a close bond with the patient, we believe that telehealth-related tools have made it easier to reduce uncertainty about the status of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have explored the impact of the COVID-19 pandemic on the practice of therapists, on mental health and the use of telerehabilitation strategies by therapists during the period of confinement ( Dogruoz Karatekin et al, 2021 ; Ganesan et al, 2021 ). As healthcare personnel who have a close bond with the patient, we believe that telehealth-related tools have made it easier to reduce uncertainty about the status of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…18,21 Some postponement of medical appointments was reported in the treatment of children and young people with CP and delays were reported in administering botulinum neurotoxin A injections, although medical appointments were more stable than access to therapies. 22,23 One study reported that these delays resulted in an almost six-fold increase in pain complaints and worsening of spasticity. 22…”
Section: Frequency Of Consultationsmentioning
confidence: 99%
“…22,23 One study reported that these delays resulted in an almost six-fold increase in pain complaints and worsening of spasticity. 22…”
Section: Frequency Of Consultationsmentioning
confidence: 99%
“…First and foremost, we would like to appreciate the authors for clearly and succinctly describing how lockdown affects people with cerebral palsy 1. The authors' ability to distinctively key out an informative and focused introduction part shall be acclaimed.…”
mentioning
confidence: 99%
“…To the Editor, First and foremost, we would like to appreciate the authors for clearly and succinctly describing how lockdown affects people with cerebral palsy. 1 The authors' ability to distinctively key out an informative and focused introduction part shall be acclaimed. The study interested us in reading more about how the COVID-19 pandemic affected physical medicine and various rehabilitative practices.…”
mentioning
confidence: 99%